2023
DOI: 10.1007/s10900-023-01197-6
|View full text |Cite
|
Sign up to set email alerts
|

Micromobility Vehicles, Obstructions, and Rider Safety Behaviors in New York City Bike Lanes

Abstract: Micromobility vehicles (MMVs) have become increasingly popular, particularly in urban areas where infrastructure has improved in recent years to facilitate their use. The purpose of this study was to observe protected bike lanes in 10 zones of Manhattan, NYC to: (1) describe the MMVs in bike lanes by type, phone and helmet use; and (2) document MMV users’ responses to obstructions. Approximately 1 in 4 of all riders (260/998) were wearing a helmet. Fewer than 2% were observed using a phone while moving. Fewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A study in New York City reported that nearly a quarter of micromobility users encountered bike lane obstructions, often diverting into vehicle traffic lanes. 32 This highlights the need for robust and better integrated bike lanes that are suitable for micromobility riders, minimizing interactions with pedestrians and motor vehicles. The enforcement of mandatory helmet laws and speed limits for EVs is also essential, as speed restrictions may reduce the number of injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in New York City reported that nearly a quarter of micromobility users encountered bike lane obstructions, often diverting into vehicle traffic lanes. 32 This highlights the need for robust and better integrated bike lanes that are suitable for micromobility riders, minimizing interactions with pedestrians and motor vehicles. The enforcement of mandatory helmet laws and speed limits for EVs is also essential, as speed restrictions may reduce the number of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Developing micromobility-friendly urban infrastructure may enhance safety for riders. A study in New York City reported that nearly a quarter of micromobility users encountered bike lane obstructions, often diverting into vehicle traffic lanes . This highlights the need for robust and better integrated bike lanes that are suitable for micromobility riders, minimizing interactions with pedestrians and motor vehicles.…”
Section: Discussionmentioning
confidence: 99%